(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Jelena Dimitrijević is better known for her literary work than for her social, patriotic and humanitarian achievements. She was a member of three women’s societies in which she actively worked. Until now, that part of Jelena Dimitrijević’s life was not fully discovered and represented a real challenge for research. Eventually, it has been revealed that she became a regular member of the Women’s Society branch in Niš for the first time in 1881 and then, after a short break, joined again in 1893, only to become an executive member in late 1894. Beginning from 1898, she became a regular member of the Belgrade Women’s Society and member of Literary Committee of the magazine Domaćica [Homemaker]. Her friendship with Ljubica Luković, also member of the Women’s Society, which began in Niš, continued in Belgrade as well. Until now, it was unknown that in 1903, Jelena became a member of the Society Knjeginja Ljubica, as shown in latest discovered data. Her work within Kolo srpskih sestara [Circle of Serbian Sisters] is slightly better known, especially her work in the magazine Vardar. During this period, she met Delfa Ivanić, the founder of Kolo srpskih sestara and so began their long-lasting friendship and collaboration in the National Women’s Alliance. Information has been found that Jelena was awarded with her first medal in 1896. She received her second medal in 1911 and the third in 1928 during the celebration of her jubilee. All of this shows that, apart from her literary work, Jelena Dimitrijević was also deeply committed to protecting the weak, children and women, as well as supporting the fight for national liberation of the Serbian people on the territory of the Ottoman Empire and Habsburg Monarchy.